2012
DOI: 10.1111/j.1744-6163.2012.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Talking About Sexuality With Consumers of Mental Health Services

Abstract: PURPOSE:  To explore nurses' perceptions of how consumers of mental health services have responded to mental health nurses discussing sexuality with them. DESIGN AND METHODS:  Qualitative exploratory design including in‐depth individual interviews with 14 mental health nurses in Australia on two occasions. Nurse participants were taught the BETTER model in the first interview and were asked to use this in their practice. FINDINGS:  In the second interview nurse participants described the model as useful and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Applying refers to nurses including sexual concerns in their assessment and care as part of their ongoing practice and beginning to value the importance of both this area of care for consumers and their role in providing this care (Quinn & Happell, 2012a, 2012bQuinn, Happell, & Welch, in press). These skills require practice (Gianotten, Bender, Post, & Hoing, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Applying refers to nurses including sexual concerns in their assessment and care as part of their ongoing practice and beginning to value the importance of both this area of care for consumers and their role in providing this care (Quinn & Happell, 2012a, 2012bQuinn, Happell, & Welch, in press). These skills require practice (Gianotten, Bender, Post, & Hoing, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The participants came to value the importance of sex for consumers. This led to sexual concerns becoming embedded in their professional practice, increasing their confidence in addressing this important aspect of care (Quinn & Happell, 2012). Ultimately human sexuality was acknowledged as part of their practice, an important component of holistic care (Albaugh & Kellog-Spadt, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Saunamaki et al (2010) found that although nurses felt comfortable talking about patients' sexual matters and are responsible of providing sexual health care, they still did not have confidence in their ability to deal with patients' sexual concerns. Therefore, to improve trend in provision of sexual health care, educational curricula should pay more attention to educational strategies, such as role-play opportunities (Steinke, Mosack, Barnason, & Wright, 2011) and the practice of the intervention model as guidance for sexual health care (Quinn & Happell, 2013) that can result in a positive and active attitude and self-confidence toward discussing sexual matters and providing sexual health care to patients rather than just an attitude of respect and acceptance. Individual competencies and perception of self-efficacy on sexuality could be constantly modified by environmental conditions (Hogben & Byrne, 1998), and variations in nursing practice could affect nursing students' experiences about performing sexual health care to patients (Johnston, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Recent developments in the field include recognition of the beneficial effects of a healthy sexual life in patients with severe mental disorders; the need to incorporate this aspect in assessment and management within routine clinical practice 1 ; a more in-depth understanding of the adverse effects of psychotropic drugs on sexual life; and more detailed guidelines about how to manage sexual dysfunction in these already deeply disadvantaged people.…”
mentioning
confidence: 99%